Characteristics, Origins, and Biosignature Preservation Potential of Carbonate‐Bearing Rocks Within and Outside of Jezero Crater. Issue 11 (5th November 2021) - Tarnas, J. D.; Stack, K. M.; Parente, M.; Koeppel, A. H. D.; Mustard, J. F.; Moore, K. R.; Horgan, B. H. N.; Seelos, F. P.; Cloutis, E. A.; Kelemen, P. B.; Flannery, D.; Brown, A. J.; et al.
Abstract: Carbonate minerals have been detected in Jezero crater, an ancient lake basin that is the landing site of the Mars 2020 Perseverance rover, and within the regional olivine‐bearing (ROB) unit in the Nili Fossae region surrounding this crater. It has been suggested that some carbonates in the margin fractured unit, a rock unit within Jezero crater, formed in a fluviolacustrine environment, which would be conducive to preservation of biosignatures from paleolake‐inhabiting lifeforms. Here, we show that carbonate‐bearing rocks within and outside of Jezero crater have the same range of visible‐to‐near‐infrared carbonate absorption strengths, carbonate absorption band positions, thermal inertias, and morphologies. Thicknesses of exposed carbonate‐bearing rock cross‐sections in Jezero crater are ∼75–90 m thicker than typical ROB unit cross‐sections in the Nili Fossae region, but have similar thicknesses to ROB unit exposures in Libya Montes. These similarities in carbonate properties within and outside of Jezero crater is consistent with a shared origin for all of the carbonates in the Nili Fossae region. Carbonate absorption minima positions indicate that both Mg‐ and more Fe‐rich carbonates are present in the Nili Fossae region, consistent with the expected products of olivine carbonation. These estimated carbonate chemistries are similar to those in martian meteorites and the Comanche carbonates investigated by the Spirit rover in Columbia Hills. Our results indicate that hydrothermal alteration is the most likely formation mechanism for non‐deltaic carbonates within and outside of Jezero crater. Plain Language Summary: Spacecraft orbiting Mars can measure the composition of rocks that make up its surface. Understanding rock composition allows us to interpret past environmental conditions on Mars, including their likelihood to be habitable. Using data acquired from orbit, researchers have found carbonate minerals in Jezero crater and the surrounding region—called the Nili Fossae region. Jezero crater is the landing site of NASA's Mars 2020 Perseverance rover and once contained a lake. The discovery of carbonates is exciting because on Earth they sometimes form in habitable environments and preserve fossils. In this study, we used all available high resolution orbital datasets to look at similarities and differences between carbonate‐bearing rocks within and outside of Jezero crater. We found that carbonate‐bearing rocks within and outside of Jezero crater have similar orbital properties, implying that they formed by the same processes. We found that the range in chemistries (magnesium‐rich vs. iron‐rich) for carbonates within and outside of Jezero crater is similar to carbonate chemistries found in martian meteorites and by other rovers on Mars. The carbonates within and outside of Jezero crater could have formed by the same water‐rock interactions that formed carbonates discovered in martian meteorites and by other rovers on Mars. Key Points: Carbonates within and outside of Jezero crater have similar spectra, thermal inertias, morphologies, and thicknesses Carbonates within and outside of Jezero crater likely formed via the same processes Hydrothermal alteration and evaporation are the most likely processes for carbonate formation within and outside of Jezero crater